Evaluación de la confiabilidad metrológica de manómetros tipo Bourdon utilizando el método de los mínimos cuadrados ordinarios (2021)
This project has been developed to analyze and apply a method that helps us evaluate the performance of pressure gauges, a fundamental tool in industrial processes, within the technical supports we have taken as a fundamental part the analysis and investigation and applicability of the comparison process between laboratories based on the standard error criterion, considered with great importance within this activity, the expected results of this work is to be able to guarantee the reliability of a measuring instrument such as the Bourdon type manometer that is used in most industries. . In addition, it is expected to apply the ordinary least squares method to determine an interpolating polynomial that allows obtaining tight and, consequently, reliable pressure measurements. The consolidated results allowed to conclude that the application of the least squares method allowed to conclude that the metrological performance of the pressure gauges is statistically the same for a measurement range between 0 and 30 psi, within a confidence level of 95.0%. The above indicates that the pressure gauges can be used in processes that contemplate the evaluated measurement range.